Summary of the best evidence for risk stratification of exercise rehabilitation in patients with a cardiac implantable electronic device - Di, Ruiqing; Huang, Zheng; Huang, Huifang; Li, Siyu; Gao, Xing; Bai, Jingshuang (Frontiers in Cardiovascular Medicine, 2024)
BackgroundHierarchical management of sports risk is highly critical to ensure the safety of sports rehabilitation. Early identification, timely prevention and control of sports-related risk factors, and enhanced supervision and guidance can provide a basis for the formulation of sports programmes and the setting of sports monitoring levels.ObjectiveThis study aimed to retrieve, evaluate, and integrate evidence for the stratified management of motor risk in patients with a cardiac implantable electronic device (CIED).MethodsWe searched for evidence according to the “6S” model of evidence-based resources. CNKI, VIP, Wanfang Data, CBM, PubMed, Cochrane Iibrary, CINAHL, EMbase, Web of Science, BMJ Best Practice, Up To Date, and International Guidelines Collaboration Network were searched from inception to February 2024. To search for evidence on stratified management of motor risk in patients with CIEDs, this research includes guidelines, systematic reviews, meta-analyses, expert consensus, clinical decision-making, and randomized controlled trials. After methodological quality evaluation, the evidence was extracted and summarized accordingly.ResultsAccording to the inclusion and exclusion criteria, 16 pieces of evidence were screened, including 5 guidelines, 1 clinical decision-making, 5 systematic reviews, 4 expert consensus, and 1 randomized controlled trial. After reading, extracting, and categorizing, 34 pieces of evidence in 4 areas were identified, namely, screening and assessment of exercise risk in CIEDs, exercise monitoring, implementation of exercise prescriptions, and prevention and management of exercise-related risks.ConclusionsThis study provides the best evidence for the prevention and management of exercise risk in patients with CIEDs, clarifies the role of nurses in evaluating, monitoring, and educating patients undergoing motor rehabilitation, and provides a basis for the formulation of clinically feasible rehabilitation programs.Systematic Review RegistrationPROSPERO, identifier (CRD2024509622).